2019
DOI: 10.3390/toxins11030151
|View full text |Cite
|
Sign up to set email alerts
|

Mycotoxins and Related Fungi in Italian Paddy Rice During the Growing Season and Storage

Abstract: Mycotoxigenic fungi and relative mycotoxins contamination were monitored in Italian paddy rice samples both in field during the growing season and the first five months of storage. Three experimental fields, nine rice varieties and three sowing densities were considered; then, different lots of paddy rice were stored in warehouses at different temperature regimes. Fusarium spp. and Aspergillus spp. were found to be the fungi most likely to produce mycotoxins throughout the growing season. In particular, A. fla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
20
0
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 25 publications
(29 citation statements)
references
References 30 publications
6
20
0
3
Order By: Relevance
“…Among the considered mycotoxins considered, OTA and AFs were never detected; DON was found in 46% of the samples at levels always lower than 100 µg/kg, while STC occurred in almost all the paddy rice samples, showing a maximum value of 15.5 µg/kg. These data partially accord with a previous study, carried out on rice samples collected in the same area, that found DON and AFs only sporadically and in low amounts, while STC was always detected, appearing as crucial in rice contamination [10].…”
Section: Resultssupporting
confidence: 92%
See 4 more Smart Citations
“…Among the considered mycotoxins considered, OTA and AFs were never detected; DON was found in 46% of the samples at levels always lower than 100 µg/kg, while STC occurred in almost all the paddy rice samples, showing a maximum value of 15.5 µg/kg. These data partially accord with a previous study, carried out on rice samples collected in the same area, that found DON and AFs only sporadically and in low amounts, while STC was always detected, appearing as crucial in rice contamination [10].…”
Section: Resultssupporting
confidence: 92%
“…The highest DON contamination was found in the rice variety CL15 while the lowest was in the rice variety Centauro (Table 1); none of the rice varieties considered in the study showed a DON contamination above the limits fixed by the European Commission of 1250 µg/Kg for paddy rice (EU Regulation 1881/2006). These results seem to confirm the findings of a previous study where DON was found only in low amounts [10] suggesting that this mycotoxin could be considered a minor risk for Italian paddy rice.…”
Section: Resultssupporting
confidence: 91%
See 3 more Smart Citations